Pengambilan Keputusan Mahasiswa Dalam Memilih Indekos Di Daerah Universitas Muhammadiyah Surakarta - Ghifari, Muhammad, Dr. Nanik Prihartanti,M.Si., Psi (2017)
In indonesia, there's a lot of students who just graduated from high school continuing their study to another city, province or island. The reason to continuing their study to outside their region is because of there is no desired major in the local university, or the scholarship that require them to continuing their study in the pre-selected university. The main functions of student's boarding house is to be a temporary home, studying space, and resting place. However, from the recovered data, there's various reasons for students to move from one boarding house to another. This research aims to help the renter and the owner of the boarding house to understand better the process and factors of boarding house selection around UMS. From this research, the researcher hope the renters would understand better what they were really wants, and for the boarding house owner to understand the very factors that made their property always in demand. this research use descriptive qualitative research method. In this research, 10 informants were used and with these criteria: (a) Student of Muhammadiya University of Surakarta from year 2016, (b) live in surakarta. This research used an interview as a means to gather datas. The data were analyzed thematically. Based on research findings, there to be known that boarding house selection process consist of selecting boarding house, evaluating all the options, and planned the taken option. Meanwhile, student's boarding house selection process influenced by a few factors which is ordered by the researcher that is comfort, facility, price and distance. In the future, purposive sampling could be used so the data gathered about factors and selection process would be more distributed and could be more focused from the boarding house owner perspective.